The Choice of the Public-Private Partnership Model to Address Social and Economic Development of the State in the Context of a Competitive Environment with Uncertainty and Risks - Mekhovich, Sergey; Kolesnichenko, Anastasiia (Theory, Methodology, Practice – Review of Business and Management, 2014)
This article discusses the growing importance of public-private partnership due to modern economic conditions and extensive privatization activity. The institute of public-private partnership provides mechanisms for redistribution of risk among the subjects of new market relations. This cooperation appeared as a result of the complex development process during the last two decades. Today it plays a significant role in problem solving concerning public infrastructure development.